2019
DOI: 10.1007/978-3-030-22176-8_7
|View full text |Cite
|
Sign up to set email alerts
|

Does Participating in National and Ethnic Associations Promote Migrant Integration? A Study with Young First- and Second-Generation Migrants

Abstract: Research carried out in recent decades on the experiences of migrants in Western countries recognizes the complexity and multidimensionality of adaptive and integrative processes associated with the difficulties of living in a new sociocultural context.Following an overview of the distinctive characteristics of different migrant generations, we present a brief review of studies that connect social participation with integration and multiculturalism. In this chapter we define social participation as the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…They offer social spaces that contribute to forming social ties between different small groups of migrants who may perceive themselves to be isolated from the community they 'imagine'. In studies of migrant organisations, profit and non-profit organisations are often seen as distinct (Babis, 2016;Guma et al, 2023;Halm and Sezgin, 2013;Marzana et al, 2020;Moya, 2005). The latter are often considered to have been created to defend the interests of migrants and to maintain homeland identity and culture.…”
Section: Discussion: Cultural Reproduction In Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…They offer social spaces that contribute to forming social ties between different small groups of migrants who may perceive themselves to be isolated from the community they 'imagine'. In studies of migrant organisations, profit and non-profit organisations are often seen as distinct (Babis, 2016;Guma et al, 2023;Halm and Sezgin, 2013;Marzana et al, 2020;Moya, 2005). The latter are often considered to have been created to defend the interests of migrants and to maintain homeland identity and culture.…”
Section: Discussion: Cultural Reproduction In Communitymentioning
confidence: 99%
“…In migration studies, there remains a popular view that migrant communities are often built through informal and formal organisations, that aim to fulfil their members' needs, including preserving their 'true' or 'original' culture and heritage, promoting common goals and interests or contributing to developing social trust and support (Babis, 2016;Fennema, 2004;Halm and Sezgin, 2013;Jardim and Da Silva, 2019;Marzana et al, 2020). Community members are commonly perceived as being linked through horizontal connections, such as those formed through participation in organisational activities and extended through intergroup membership and contacts.…”
Section: Community and Migrants' Culturementioning
confidence: 99%
“…Specifically, MCBOs are settings where immigrants can resist injustice (Buckingham et al, 2021), share oppressive experiences, bolster collective dignity, and take action to transform their realities (Aceros et al, 2021; Paloma et al, 2010). Although research has found a bidirectional relationship between psychological sense of community and community participation (Chavis & Wandersman, 2002; Talò et al, 2014), in this study—following our liberation psychology theoretical approach—we are interested in analyzing community participation as a catalyzer of psychological sense of community among immigrants (Marzana, Alfieri, Marta, 2020; Marzana, Alfieri, Marta, Paloma, 2020; Marzana, Martinez Damia, et al 2020; Ramos et al, 2017, 2020; Sonn, 2002). We also relied on the literature on the general population that reported that psychological sense of community could serve as both a partial and a total mediator between community participation and subjective wellbeing (Cicognani et al, 2008; Mazzoni et al, 2014) and similar results that were found for immigrants (Liu, 2020).…”
Section: Mediators Between Community Participation and Subjective Wel...mentioning
confidence: 99%